Development of the Glossopteris flora and its end Permian demise in the Tatapani–Ramkola Coalfield, Son–Mahanadi Basin, India. (10th August 2018) - Saxena, Anju; Singh, Kamal Jeet; Cleal, Christopher J.; Chandra, Shaila; Goswami, Shreerup; Shabbar, Husain
Abstract : Diverse macrofloral assemblages recovered from the Barakar, Raniganj, and Panchet formations of Tatapani–Ramkola Coalfield have been analysed. Plant fossils from nine localities represent typical Glossopteris floras of Permian age with Glossopteris as the dominant genus (33 species), whereas younger floral elements recorded from five locations are characterized by the presence of Triassic species, i.e., Glossopteris senii and G .  gopadensis along with the genus Dicroidium . The complete flora includes 24 genera and 73 species. Three floristic assemblages identified on the basis of the macrofloras are the Barakar assemblage with 31 taxa, the Raniganj assemblage with 38 taxa, and the Panchet assemblage having 33 taxa. All the available data concerning megaplant remains, palynology, and petrology of this basin are reviewed and analysed to infer the diversity trends of Glossopteris flora through the sequence and its transformation at the Raniganj–Panchet boundary (?Permian/Triassic boundary) in this coalfield. The Barakar Formation has a moderate diversity of Glossopteris (18 species), which increases in Raniganj Formation (26 species) and declines in the Panchet Formation (16 species). There is a gradual upwards change in the taxonomic composition of the Raniganj assemblage, with a decline in diversity, although some typical Permian taxa (e.g., Paracalamites, Schizoneura, Dizeugotheca, Glossopteris, and Vertebraria ) continued up to the Panchet Formation. In India, the continental Permian–Triassic boundary has been resolved mainly on the basis of palynomorph and macrofloral data and is conventionally taken to coincide with the boundary between the Raniganj and Panchet formations. The Raniganj–Panchet boundary has been tentatively proposed in one of the sections of this coalfield. At this boundary, the Glossopteris species typical of the Raniganj Formation (i.e., G .  stenoneura and G .  stricta ) disappear. Some of the Glossopteridales taxa, continuing into the Panchet Formation, show relatively little discernable change from those found in the Raniganj Formation. The Panchet Formation exhibits a dominance of Dicroidium and also marks the appearance of ? Autunia, Heidiphyllum, Lepidopteris, Linguifolium, and Rissikia . Therefore, it is envisaged that plant life was only gradually transformed and evolved near this boundary, rather than being the subject of a comprehensive taxonomic turnover. The genus ? Autunia is reported for the first time from Indian Gondwana.